Influence of Polymeric Fiber Reinforcement on Strength Properties of Sand-stabilized Expansive Soil - Oncu, Serife; Bilsel, Huriye (Taylor & Francis Inc, 2017)
This paper presents the findings of an experimental study on improvement of strength properties of sand-stabilized expansive soil, reinforced with polymeric fiber which consists of pipe scrap waste obtained as a by-product of construction industry. Sand is mixed in 1:1 ratio with expansive soil forming a stable structure with improved stability. Enhancement of strength properties is provided by the addition of polymeric fiber of 1, 2, and 3% by dry mass, and the results indicated that compressive, split tensile, and flexural strengths improved by an optimum amount of 2%. Consequently, an area for recycling this nonbiodegradable waste is also proposed.
Keywords: Compacted sand-expansive soil; compressive strength; flexural strength; polymeric fiber; split tensile strength